1996
DOI: 10.1002/(sici)1097-461x(1996)59:3<183::aid-qua2>3.0.co;2-u
|View full text |Cite
|
Sign up to set email alerts
|

Eigenvalues of the two-dimensional Schr�dinger equation with nonseparable potentials

Abstract: mThe energy eigenvalues of coupled oscillators in two dimensions with quartic and sextic couplings have been calculated to a high accuracy. For this purpose, unbounded domain of the wave function has been truncated and various combination of trigonometric functions are employed as the basis sets in a Rayleigh-Ritz variational method. The method is applicable to the multiwell oscillators as well. 0 1996 John Wiley & Sons, Inc.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
19
0

Year Published

1996
1996
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 14 publications
3
19
0
Order By: Relevance
“…Our results, see Tables I -IV, are in complete agreement with [6], [10] for D = 1 and superior considerably of those obtained for D > 1 and different g 2 , see e.g. [11], [12] and [13].…”
Section: The Approximant and Variational Calculationssupporting
confidence: 90%
See 2 more Smart Citations
“…Our results, see Tables I -IV, are in complete agreement with [6], [10] for D = 1 and superior considerably of those obtained for D > 1 and different g 2 , see e.g. [11], [12] and [13].…”
Section: The Approximant and Variational Calculationssupporting
confidence: 90%
“…In general, our results reproduce all known numerical ones that can be found for D = 1, 2, 3, see e.g. [12], [11] [18] and [19].…”
Section: The Approximant and Variational Calculationssupporting
confidence: 90%
See 1 more Smart Citation
“…In a recent article [13] by the same authors, it was shown numerically that the Dirichlet boundary value problem,…”
Section: Introductionmentioning
confidence: 99%
“…Thus, we expand the wave functions in terms of the trigonometric basis functions obeying Dirichlet boundary condition. Then we use the Rayleigh-Ritz variational scheme to optimize the domain of the basis functions which leads to highly accurate solutions [6][7][8][9][10]. …”
Section: Introductionmentioning
confidence: 99%